2020
DOI: 10.2196/preprints.26049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FOCUS mHealth Intervention for Veterans With Serious Mental Illness in an Outpatient Department of Veterans Affairs Setting: Feasibility, Acceptability, and Usability Study (Preprint)

Abstract: BACKGROUND Veterans with serious mental illnesses (SMI) face barriers to accessing in-person evidence-based interventions that improve illness management. Mobile health (mHealth) has been demonstrated to be feasible, acceptable, effective, and engaging among individuals with serious mental illness in community mental health settings. mHealth for SMI has not been tested within the VA. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…mHealth support specialists are human support personnel embedded within clinical settings that help users interact with mHealth technologies, and could help socialize patients to mental health apps. Models have been tested with nonclinical personnel who are trained specifically to perform the role of support of specialist (e.g., Buck et al, under review; Graham et al, 2020), as well as licenced mental health clinicians who perform this role in addition to other clinical duties (Mohr et al, 2019; Possemato et al, 2016). Researchers have begun examining the mHealth support specialist model in real-world clinical settings, and have found that its implementation results in significant improvement in symptoms of depression and anxiety compared to treatment as usual in a primary care setting (Graham et al, 2020; Possemato et al, 2016), as well as increased app use compared to a control of only providing information about the app (Possemato et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…mHealth support specialists are human support personnel embedded within clinical settings that help users interact with mHealth technologies, and could help socialize patients to mental health apps. Models have been tested with nonclinical personnel who are trained specifically to perform the role of support of specialist (e.g., Buck et al, under review; Graham et al, 2020), as well as licenced mental health clinicians who perform this role in addition to other clinical duties (Mohr et al, 2019; Possemato et al, 2016). Researchers have begun examining the mHealth support specialist model in real-world clinical settings, and have found that its implementation results in significant improvement in symptoms of depression and anxiety compared to treatment as usual in a primary care setting (Graham et al, 2020; Possemato et al, 2016), as well as increased app use compared to a control of only providing information about the app (Possemato et al, 2016).…”
Section: Discussionmentioning
confidence: 99%